(untitled) (Journal of the College of Basic Education, 2023)
The importance of the current research was determined in the light of several factors, the most important of which are:1- The childhood stage, being the most important stage of growth in the formation of the human personality.The subject of child care and healthy and natural growth is extremely important.Contribute to building a righteous generation.2- The researchers felt the importance of studying the behavioral manifestations of students in the primary school due to the large number ofHesitation in the councils of teachers and parents about the behavior of students, which is positive and negativeAnd the interest of all those involved in the affairs of education the need to understand the behavior of students.3- The researchers sensed the need to identify the existing behavioral manifestations of studentsprimary school and building a scale that becomes accessible to teachers to assess their behavior and sortThose of them who need to consult a psychiatrist for referral, follow-up of their condition and prevent its development intoDifficult behavioral problems to treat in the future, as well as improving the learning and guidance processand guidance.4- Knowing the behavioral manifestations of students is useful to the teacher to study the dimensions of growth in its various aspects.It helps in defining programs and activities that help in their proper development as well asIts impact on presenting the educational methods that are adopted in their upbringing.5- Knowing the behavioral manifestations of students, whether positive or negative by the teacher.Help to create a state of natural agreement between him and the student, and thus achieve good adaptationthem, which clearly affects their general development. The successful teacher considers himself responsible for allThe responsibility is to achieve for his student the ability to have good social and emotional compatibility.6- Through this research, it is possible to identify the common behavioral manifestations of the students in the study.elementary school, down to a good understanding of their personality characteristics, and therefore the existence of an appropriate scaleFor this purpose, it is characterized by an acceptable degree of validity and stability, which facilitates the possibility of reaching a judgment.